Activation of the Akt‐mTOR pathway and receptor tyrosine kinase in patients with solitary fibrous tumors. Issue 6 (18th December 2013) - Yamada, Yuichi; Kohashi, Kenichi; Fushimi, Fumiyoshi; Takahashi, Yusuke; Setsu, Nokitaka; Endo, Makoto; Yamamoto, Hidetaka; Tokunaga, Shoji; Iwamoto, Yukihide; Oda, Yoshinao
<x xml:space="preserve">Abstract</x> BACKGROUND Solitary fibrous tumors (SFTs) are soft tissue tumors of intermediate malignancy that rarely metastasize. Although unresectable SFTs are reported to have a poor prognosis, to the authors' knowledge there is currently no effective therapy. Molecular target therapy is a promising approach for patients with unresectable tumors, but knowledge of the molecular biology of SFTs is currently insufficient to support such therapy. The current study investigated the activation of receptor tyrosine kinases (RTKs) and the Akt‐mammalian target of rapamycin (Akt‐mTOR) pathway in SFTs as therapeutic targets. METHODS The phosphorylation statuses of Akt‐mTOR pathway proteins (p‐Akt, p‐mTOR, phosphorylated 4E‐binding protein [p‐4EBP1], and phosphorylated S6 ribosomal protein [p‐S6RP]) and RTKs (phosphorylated platelet‐derived growth factor receptor‐α [p‐PDGFRα], p‐PDGFRβ, p‐c‐met, and phosphorylated insulin‐like growth factor‐1 receptor‐β [p‐IGF‐1Rβ]) were assessed by immunohistochemistry in 66 samples of SFTs, and the data were compared with clinicopathological and histopathological findings. The expression of phosphorylated proteins was assessed by Western blot analysis in 6 frozen samples. RESULTS The immunohistochemical results were as follows: p‐Akt, 56.0% (nuclear and cytoplasmic staining); p‐mTOR, 69.6% (nuclear and cytoplasmic staining); p‐4EBP1, 80.3% (nuclear and cytoplasmic staining); p‐S6RP, 69.6% (cytoplasmic staining); p‐PDGFRα, 39.0% (cytoplasmic staining); p‐PDGFRβ, 52.0% (cytoplasmic staining); p‐c‐met, 37.8% (nuclear staining) and 19.6% (cytoplasmic staining); and p‐IGF‐1Rβ, 16.6% (nuclear staining). Phosphorylation of the Akt‐mTOR pathway proteins was correlated with one another except for p‐Akt with S6RP. p‐PDGFRβ and p‐IGF‐1Rβ were correlated with p‐Akt. Moreover, significant relationships were noted between disease‐free survival or overall survival and the presence of hypoglycemia, necrosis, cystic and myxoid degeneration, and atypical findings. CONCLUSIONS The Akt/mTOR pathway was activated in approximately 50% of the cases of SFTs and was associated with RTKs, which were phosphorylated at different rates. Thus, the Akt‐mTOR pathway may be involved in the tumorigenesis of SFTs. Cancer 2014;120:864–876. © 2013 American Cancer Society.